What is the Value of Foreign Work Experience? Analysing Online CV Data in Slovakia - Lucia Mýtna Kureková; Zuzana Žilinčíková (Institute for the Study of Labor (IZA), 2016)
This paper studies how attractive young returnees are in the labour market and how they behave relative to stayers. We use the online CVs of young people that are posted on the major Slovak job-search portal. The analysis is performed using a set of regression models that investigate attractiveness, salary expectations and positions of interest to returnees in comparison to stayers. We find that the post-accession foreign work experience increases the attractiveness of job candidates, but that attractiveness premium varies depending on the returnee's host country. Returnees are more demanding with respect to their minimum salary expectations and are more likely than stayers to apply for positions advertised abroad. Return migrants are a diverse group - women, graduates, or people returning to economically underperforming regions, continue to face disadvantages with labour market integration.
Keywords: F22; J23; 330; return migrants; employers; web data; labour market; integration; Slovakia